Endovascular brachytherapy with iodine-125 seed strand for extensive portal vein tumor thrombus in patients with hepatocellular carcinoma - Tan, Zhongbao; Wu, Daguang; Guo, Jinhe; Wang, Huanjing; Zhang, Jian (Frontiers in Oncology, 2023)
Objective The aim of this study is to investigate the feasibility and effectiveness of endovascular brachytherapy with iodine-125 (I-125) seed strand for the treatment of extensive portal vein tumor thrombus (PVTT) in hepatocellular carcinoma (HCC) patients. Methods A total of 40 HCC patients complicated by extensive PVTT who received I-125 seed strand implantation from January 2015 to December 2022 in our center were analyzed retrospectively. Endpoints included technical success rate, concurrent therapies, overall survival time, and complications. Multivariate and subgroup analyses were conducted for overall survival. Results The successful rate of operation was 100%, and there was no operation-related death. A total of 37 patients received single I-125 seed strand implantation, and three patients received double I-125 seed strand implantation. A total of 23 patients received a concurrent therapy: transarterial chemoembolization (TACE) combined with systematic treatment (n = 6), TACE alone (n = 10), and systematic treatment alone (n = 9). At a median follow-up of 3.5 (interquartile range (IQR), 2~8.5) months, the median overall survival (OS) of all patients was 92 days (95% confidence interval (CI): 77~108). In the subgroup analysis, the median OS was 128 days (95% CI: 101~155 days) in the I-125 seed strand implantation plus systematic treatment group and was longer than that (75 days (95% CI: 36~114) of the I-125 seed strand alone group (p = 0.037). Multivariate analysis revealed that no systematic treatment was an independent risk factor affecting the prognosis in this study. Six patients died of upper gastrointestinal bleeding: four patients in the I-125 seed strand alone group and two patients in the combination of I-125 seed strand with systematic treatment group. Conclusions The study shows that endovascular brachytherapy with I-125 seed strand implantation is a safe and effective treatment method for extensive PVTT in HCC patients. The combination of I-125 seed strand implantation and systematic treatment can prolong the survival time.